Long-read sequencing to resolve the parent of origin of a de novo pathogenic UBE3A variant. Issue 11 (12th April 2022) - Watson, Christopher Mark; Jackson, Lucy; Crinnion, Laura A; Bonthron, David T; Sheridan, Eamonn
Abstract : Background The ever-increasing capacity of short-read sequencing instruments is driving the adoption of whole genome sequencing (WGS) as a universal approach to the diagnosis of rare genetic disorders. However, many challenging genomic regions remain, for which alternative technologies must be deployed in order to address the clinical question satisfactorily. Methods Here we report the use of long-read sequencing to resolve ambiguity over a suspected diagnosis of Angelman syndrome. Results Despite a normal chromosomal microarray result and methylation studies at the imprinted 15q11q13 locus, the continued clinical suspicion of Angelman Syndrome prompted trio WGS of the proband and his parents. A de novo heterozygous frameshift variant, c.2370_2373del (NM_130838.2) p.(Asp790Glufs*7), in UBE3A was identified. To determine the parental allele on which this variant arose, long-read sequencing of the flanking genomic region was performed. Comparison of the resulting haplotypes allowed us to determine that the pathogenic frameshift variant arose on the maternal allele, confirming a diagnosis of Angelman syndrome in this case. Conclusion Long-read nanopore sequencing provides significant clinical utility when assessing the parental origin of de novo variants.